2013
DOI: 10.1016/j.metabol.2012.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an overnight intravenous lipid infusion on intramyocellular lipid content and insulin sensitivity in African–American versus Caucasian adolescents

Abstract: Objective To explain the predisposition for insulin resistance among African American (AA) adolescents, this study aimed to: 1) examine changes in intramyocellular lipid content (IMCL), and insulin sensitivity with intralipid (IL) infusion; and 2) determine whether the increase in IMCL is comparable between AA and Caucasian adolescents. Materials and Methods Thirteen AA and 15 Caucasian normal-weight adolescents (BMI <85th) underwent a 3-h hyperinsulinemic-euglycemic clamp, on two occasions in random order, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 31 publications
1
21
1
Order By: Relevance
“…Typically, this results in elevated plasma FFA levels up to the millimolar range (compared with 200-300 μmol under control conditions). These studies have robustly and consistently shown that infusion of lipid emulsions results in a significant increase in IMCL content (Bachmann et al, 2001;Brechtel et al, 2001a;Brehm et al, 2010;Hoeks et al, 2012;Lee et al, 2013) in the type I and type II muscle fibers of healthy male individuals and highly trained athletes (Phielix et al, 2012). In these lipid emulsion infusion studies, the increase in IMCL content was paralleled by a decrease in insulin-stimulated glucose uptake in muscle.…”
Section: High-fat Diet and Lipid Infusionmentioning
confidence: 83%
“…Typically, this results in elevated plasma FFA levels up to the millimolar range (compared with 200-300 μmol under control conditions). These studies have robustly and consistently shown that infusion of lipid emulsions results in a significant increase in IMCL content (Bachmann et al, 2001;Brechtel et al, 2001a;Brehm et al, 2010;Hoeks et al, 2012;Lee et al, 2013) in the type I and type II muscle fibers of healthy male individuals and highly trained athletes (Phielix et al, 2012). In these lipid emulsion infusion studies, the increase in IMCL content was paralleled by a decrease in insulin-stimulated glucose uptake in muscle.…”
Section: High-fat Diet and Lipid Infusionmentioning
confidence: 83%
“…During subsequent intravenous insulin stimulation, inhibitory serine-1101 phosphorylation of the insulin receptor substrate-1 (pIRS1-Ser1101) was higher, while phosphatidylinositol 3-kinase (PI3K) and protein kinase B (PKB, Akt) phosphorylation were lower and associated with peripheral insulin resistance (FIGURE 3). Prolonged lipid infusion for 48 -90 h confirmed impaired insulin signaling (231) and stimulated inflammatory pathways, but did not seem to affect DAG, ceramides, or acylcarnitines (179,195). This might be due to the transient nature of the accumulation of lipid metabolites in muscle during lipid infusions (380).…”
Section: Lipid-induced Insulin Resistancementioning
confidence: 87%
“…Subsequent studies addressed the mechanisms underlying the inhibition of insulin-stimulated glucose transport and phosphorylation in human muscle biopsies (FIGURE 3). In general, lipid infusions increased total diacylglycerols (DAG) (184,277,380) and TAG (231), while only one study reported elevated ceramides (366). Fatty acid composition and compartmentalization of the specific lipid metabolites seem to determine lipid-induced insulin resistance.…”
Section: Lipid-induced Insulin Resistancementioning
confidence: 99%
“…liver, heart and skeletal muscles), was termed lipotoxicity and it is acknowledged as a major factor that causes dysfunctions in insulin signaling [17,18,19]. Moreover, it was demonstrated that even a short, overnight intravenous lipid infusion leads to a significant elevation in the intracellular lipid content (IMCL) and subsequent reductions in muscular insulin sensitivity [20]. Nonetheless, the exact cellular mechanism of the action of lipids still needs to be determined.…”
Section: The Lipid-centric View Of Insulin Resistancementioning
confidence: 99%